ORGANOCHLORINE EXPOSURES AND COGNITIVE FUNCTION IN OLDER LIFE: THE ROLE OF RACE/ETHNICITY. (20th December 2022) - Chanti-Ketterl, Marianne; Aranda, Maria; Plassman, Brenda
Abstract: Organochlorines (OCs) are persistent pesticides that remain in the environment and body for extended periods after exposure. Little is known about their long-term impact on cognition in later life. Some studies, but not all, have shown that higher levels of selected OCs are associated with lower cognitive function (CF). Using weighted linear generalized estimating equations, we explored whether the association between lipid-adjusted levels of 8 OCs and global CF is modified by race/ethnicity in 985 adults age 60+ from the National Health and Nutrition Examination Surveys (2011-2014). Adjusting for covariates, results indicated that higher levels of grouped-OCs are not associated with lower CF (p=0.121), but higher levels of specific OCs were associated with lower CF: Mirex[p=0.029]; Oxychlordane[p=0.036]; p, p'-DDE[p=0.009]; p, p'-DDT[p=0.003]; and trans-Nonachlor[p=0.023]. These associations did not differ by race/ethnicity. Disentangling the complex impact of OCs on late-life cognition—whether in combination or singularly—may lead to more equitable environmental health policies.